If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 4 = 3y + 6 Reorder the terms: 4 + 4x = 3y + 6 Reorder the terms: 4 + 4x = 6 + 3y Solving 4 + 4x = 6 + 3y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 4x = 6 + -4 + 3y Combine like terms: 4 + -4 = 0 0 + 4x = 6 + -4 + 3y 4x = 6 + -4 + 3y Combine like terms: 6 + -4 = 2 4x = 2 + 3y Divide each side by '4'. x = 0.5 + 0.75y Simplifying x = 0.5 + 0.75y
| Log[9]5+log[9]4= | | 7.3=(2x)/(.3-x) | | X/5=x-7/7 | | 3/17x=-6 | | 15x^4+6x^2-18x^3= | | n/-1.8=2.1 | | 7x+8=9-(4x-9) | | -16x^2+1000x+3=9 | | 4x+y=225 | | -3=4w | | 3y-6=21x | | 7j+14=16 | | z=20*x | | X^1/2-8=0 | | 2x-2+6x-10=180 | | 4x+6=7x+12 | | 2-8(3-6x)=0 | | 4(x-3)=3-(x+5) | | x+3/5-7=2 | | 1.5cosx(0.5-cosx)=0 | | 7-5(2x+9)=4 | | 2x-7+x+1=180 | | 10=y*20 | | 4b^2-6+10b=0 | | 7+(2x*4)=(x*-18)+2 | | 2t^2+5t+2=2 | | 4x-8=2x-3+3x-5 | | 8([15-y]/7)=-11-5y | | x(2x-4)= | | (x+5)(4x-1)+2(2-8x)(x-5)=0 | | 3x+7x+21=-29 | | (x-5)(4x-1)+2(2-8x)(x-5)=0 |